Сучасні високі технології: особливості використання для самостійної освіти - Козлакова Галина; Kozlakova Galina (ДНУ «Інститут модернізації змісту освіти», 2019)
Резюме. Статтю присвячено аналізу можливостей сучасних мобільних засобів та різних Інтернетплатформ щодо їх використання для освітніх потреб, вивчення іноземних мов, підготовки до зовнішнього незалежного тестування або підвищення економічної грамотності. Представлено характеристики нових моделей смартфонів, розглянуто можливості їх використання як навчальних засобів. Здійснено огляд он-лайн сервісів, що пропонуються для підготовки до ЗНО, зокрема з математики, української мови, англійської мови. Звертається увага на необхідність підготовки учнів і студентів до використання електронних засобів фінансового та економічного призначення. Зазначається, що для педагогів необхідним стає постійне слідкування за негативними проявами надмірного захоплення інформаційними технологіями та опрацювання нових методів їх подолання. Настав час, коли про все це можна прочитати у газетних виданнях, в яких журналісти із задоволенням розповідають про свій досвід і надають поради тим, хто не має багато часу на самоосвіту. Методичне опрацювання цих публікацій і створення україномовних посібників надає можливість молодим викладачам будувати свої тематичні уроки і лекції з використанням новітніх технологій.

Резюме. Статья посвящена анализу возможностей современных мобильных средств и различных Интернет-платформ с точки зрения их применения для образовательных целей, например, подготовки к независимому внешнему тестированию, изучения иностранных языков, повышения уровня экономической грамотности. Представлены характеристики новых моделей смартфонов, рассмотрены возможности их использования в учебном процессе. Выполнен обзор онлайн сервисов, которые предлагаются для подготовки к внешнему независимому тестированию, в том числе по математике, украинскому языку, английскому языку. Подчеркивается необходимость подготовки учеников и студентов к использованию электронных средств финансового и экономического назначения. Отмечается, что педагогам необходимо постоянно отслеживать негативные проявления чрезмерного увлечения информационными технологиями и искать возможности для их устранения. Настало время, когда об этом можно прочитать в газетных изданиях, где журналисты с удовольствием рассказывают о своем опыте и дают советы тем, у кого не достаточно времени на самообразование. По мнению автора, методическая обработка этих публикаций и создание украиноязычных пособий дает возможность молодым преподавателям подготовить свои уроки и лекции с использованием новейших технологий обучения.

Abstract. An article is devoted to analyses of possibilities of modern mobile meansand Internet resources using for educational purposes such as: preparation for independence external testing, foreign language study, increase of economicalcompetence so on. There are represented some characteristics of new models of smartphones and discussed possibilities of their using as educational means. It was shown a review of some services that are using for preparation of youth to an external independent testing (EIT) before entering to universities. These are means for preparation to EIT in Mathematic, Ukrainian, English and others.It is discussed a problem of preparation of students and schoolchildren for using of electronic means for economic and financial purposes. One of this problem is a tendency of liquidation of using cash money in some European countries. Teachers of secondary schools and professors of universities must remember about negative influences of information technolo giesand creation of methodological means for their liquidation. It is very important to continue of postgraduate and postdiplome education for active teachers and educators, their participation in Web-seminars, on-line lections and other Internet services that are possible for using in everyday practice. Self education of any person by using of different Internet resources is a modern way for the best work employment and self realization in society. This is a time when it is possible to read about this in newspapers. Journalists are writing about their experience and giving their advices for everybody who does not have enough time for self education. By author‟s mind, methodological preparation of these publications and writing of Ukrainian language handbooks can help to young educators in creation of their new lections and lessons so as in occupation of newest teaching information technologies.
Современные высокие технологии: особенности применения для самостоятельного образования
Modern High Technologies: Specifically Using for Self Education
https://drive.google.com/file/d/1ZqFlBiMZzSpZUnUgeE8o7Xui_tIA_FlZ/view
Keywords: мобільні засоби; Інтернет-засоби; самоосвіта; мобильные средства; Интернет-ресурсы; самообразование